2019
DOI: 10.7554/elife.43646
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin/γ-secretase-dependent EphA3 processing mediates axon elongation through non-muscle myosin IIA

Abstract: EphA/ephrin signaling regulates axon growth and guidance of neurons, but whether this process occurs also independently of ephrins is unclear. We show that presenilin-1 (PS1)/γ-secretase is required for axon growth in the developing mouse brain. PS1/γ-secretase mediates axon growth by inhibiting RhoA signaling and cleaving EphA3 independently of ligand to generate an intracellular domain (ICD) fragment that reverses axon defects in PS1/γ-secretase- and EphA3-deficient hippocampal neurons. Proteomic analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 65 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…NMIIA also mediates growth cone collapse and neurite retraction in response to repulsive guidance molecule (RGMa) [82]. In the case of ephrin-A5, a non-permissive molecule, by binding to EphA3 it triggers the activation of RhoA/ROCK activating NMIIA and ultimately leading to axon repulsion [92]. This context-specific role of NMIIA/B response to different guidance cues is certainly the subject of the intricate regulation, balance and spatial distribution of both NMII isoforms.…”
Section: Nmiia and Nmiib Play Central Roles In Axon Guidancementioning
confidence: 99%
“…NMIIA also mediates growth cone collapse and neurite retraction in response to repulsive guidance molecule (RGMa) [82]. In the case of ephrin-A5, a non-permissive molecule, by binding to EphA3 it triggers the activation of RhoA/ROCK activating NMIIA and ultimately leading to axon repulsion [92]. This context-specific role of NMIIA/B response to different guidance cues is certainly the subject of the intricate regulation, balance and spatial distribution of both NMII isoforms.…”
Section: Nmiia and Nmiib Play Central Roles In Axon Guidancementioning
confidence: 99%
“…Which are the roles of NMIIs in axon growth? Genetic and pharmacological studies have shown a critical role, and sometimes even opposite functions, of NMII isoforms in neuronal adhesion and growth cone dynamics [ 28 , 29 , 59 , 60 , 61 , 62 , 63 ] ( Figure 2 ). NMIIA is a downstream effector of the Rho GTPase signaling pathway during neurite retraction [ 64 ].…”
Section: Functions Of Non-muscle Myosin II In the Nervous Systemmentioning
confidence: 99%
“…NMIIA is a downstream effector of the Rho GTPase signaling pathway during neurite retraction [ 64 ]. Disruption of NMIIA activity induces a rearrangement of the actin cytoskeleton and loss of focal contacts that leads to an increase of axon length in DRG neurons [ 28 , 63 , 65 , 66 ], whereas overexpression of a non-phosphorylable NMIIA mutant that promotes myosin assembly impairs axon elongation in hippocampal neurons [ 59 ]. By contrast, NMIIB facilitates neurite and axon growth, as revealed by decreased neurite outgrowth by NMIIB knockdown in neuroblastoma cells [ 63 , 65 ], and impaired axonal outgrowth and growth cone morphology in Myh10 knockout mice [ 55 ].…”
Section: Functions Of Non-muscle Myosin II In the Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Presenilin is the catalytic subunit of γ-secretase and these mutations alter the cleavage of the Amyloid Precursor Protein (APP), which is at least partially responsible for AD pathology (35), though this has remained controversial (37). Despite clear clinical relevance, the biological functions of Presenilin and γ-secretase remain incompletely understood among roles in cell-cell signaling (33), axon guidance (38), vesicle cycling (39,40), and neuronal development (41)(42)(43). Our identification of Psn and Nct in a genetic screen raised the intriguing possibility that γ-secretase could promote postsynaptic maturation via the mechanism of Fz2 cleavage.…”
Section: An In Vivo Screen To Identify Proteases Involved In Synapticmentioning
confidence: 99%